Two new species of the predaceous midge genus Amerohelea Grogan and Wirth from Argentina (Diptera: Ceratopogonidae) - Gaddi, Ana Laura (2011)
Two new species of the predaceous midge genus Amerohelea Grogan and Wirth are described and illustrated from Argentina: Amerohelea paranaensis, Gaddi, Spinelli and Grogan, new species, from the subtropical forest zone of Misiones Province, and Amerohelea xerophila, Gaddi, Spinelli and Grogan, new species, from arid regions in San Luis, Córdoba and Río Negro provinces. The male of A. paranaensis exhibits a tuft of stout setae on the ventral surface of tarsomere 1 of the foreleg, a character previously unknown in the genus. A key is provided for males and females of all species of Amerohelea.